2017
DOI: 10.1111/coep.12214
|View full text |Cite|
|
Sign up to set email alerts
|

Fueling Job Engines: Impacts of Small Business Loans on Establishment Births in Metropolitan and Nonmetro Counties

Abstract: This study examines the effect of small business loans on subsequent establishment births in U.S. counties. Using an economic growth framework and cross‐sectional empirical model, we test the hypothesis that the establishment birth rate is higher in counties where the level and annual increase in lending is greater, controlling for community‐level characteristics affecting business and economic dynamics. We also consider the long‐term effect of small business lending and focus on establishing the appropriate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The concentration of financial services has a significant positive relationship on all quantiles less than or equal to 0.50 (Table ), but the percentage impact monotonically decreases over this quantile range (Table ). This implies greater access to a robust financial services sector benefits lower‐income entrepreneurs more than higher‐income entrepreneurs and is consistent with Conroy, Low, and Weiler ().…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The concentration of financial services has a significant positive relationship on all quantiles less than or equal to 0.50 (Table ), but the percentage impact monotonically decreases over this quantile range (Table ). This implies greater access to a robust financial services sector benefits lower‐income entrepreneurs more than higher‐income entrepreneurs and is consistent with Conroy, Low, and Weiler ().…”
Section: Resultssupporting
confidence: 86%
“…Collectively these results imply that regional agglomeration offers relatively more benefits to higher income entrepreneurs. As an exception to this general rule, the concentration of financial services within a PUMA is positive and statistically significant only at quantiles less than or equal to the 0.50 quantile, indicating that an increased availability of financial services primarily benefits lower income entrepreneurs as noted in recent research by Conroy et al ().…”
Section: Resultsmentioning
confidence: 72%
“…While these banking centralization processes may have increased some, but not all (Alessandrini et al, 2009) aspects of bank efficiency (Berger et al, 2017;Belluci et al, 2019), the firms which often appear to have been relatively disadvantaged by these changes are SMEs (Berger and Udell, 1995;Berger et al, 2004Berger et al, , 2017Canales and Nanda, 2012), and particularly those in more distant locations (Degryse and Ongena, 2005;Jiménez et al, 2009). After controlling for possible endogeneity via the use of differential lag structures (Conroy et al, 2017), system-GM methods (Hasan et al, 2019), or sample selection (Mercieca et al, 2009), local relationship-type banking appears to be especially advantageous for SMEs (Mercieca et al, 2009;Conroy et al, 2017;Hasan et al, 2019). In contrast, after controlling for endogeneity and selection using instrumental variable, conditional models, and system-GMM techniques, it is clear that SMEs in places in which the local banking system is functionally distant are at a disadvantage, especially with regard to their innovation activities (Alessandrini et al, 2009(Alessandrini et al, , 2010.…”
Section: Decentralized Versus Centralized Banking Systems: Relationships or Systemsmentioning
confidence: 99%
“…To promote entrepreneurship, Low (2005) argued that bank deposits are crucial to funding loans for entrepreneurs. Conroy, Low and Weiler (2017) found that small business loans have a positive relationship with job-generating business startups, especially in rural counties. They used small business loan data reported as a requirement of the Community Reinvestment Act.…”
Section: Financial Capitalmentioning
confidence: 98%
“…Financial capital, important for entrepreneurship (Conroy, Low and Weiler, 2017), may aid in retention due to providers' ability to access loans for starting their own practice. My financial capital variable is deposits per capita, a reflection of the amount of financial assets a county has to support lending.…”
Section: Rural Wealth Creation Variablesmentioning
confidence: 99%